Thermodynamic Study on Decarbonization of Combined Cycle Power Plant - Azaria Haykal Ahmad; Prihadi Setyo Darmanto; Firman Bagja Juangsa (Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
Integrating hydrogen firing and a carbon capture plant (CCP) into a natural gas combined cycle (NGCC) power plant is a promising strategy for reducing CO2. In this study, process simulation in Aspen PLUS of hydrogen co-firing in a 40 MW turbine gas combined cycle power plant was done at an identical gas turbine inlet temperature from 0%.cal to 30%.cal. The evaluated cases were hydrogen co-firing with CCP (H2 Co-firing + CCP) and hydrogen co-firing without CCP (H2 Co-firing). The results showed a 6% CO2 emission reduction per 5% increase in hydrogen, albeit with increased NOx emissions. H2 Co-firing experienced a decrease in net power with rising hydrogen co-firing, while H2 Co-firing + CCP saw an increase but remained below Case 2 due to the energy penalty from the carbon capture plant. The capital cost of H2 Co-firing + CCP exceeds that of H2 Co-firing due to CCP usage, impacting gross revenue. The sensitivity analysis indicated that the cost of hydrogen has higher sensitivity compared to the cost of CCP. Lowering hydrogen prices is recommended to effectively reduce CO2 emissions in NGCC.